Ghazal Poetry by Peer Moin ud Din Gillani, Renowned as Lala G. - Bukhsh, Khuda; Ghumman, Muhammad Naeem; Irfan, Muhammad (sourcecoder, 2024)
Khanqah Golra is the primary school of thought of poetry and speech. Mashaikh Golra Sharif's exquisite taste in poetry and speech is a distinguishing feature. If we look at the poetic service of the Mashaikhs of Golra Sharif, it seems that they have been given an abundant share of the heritage of the Chisht dynasty. The poetic tradition of Khanqah Golra Sharif contains many verses. Pir Meher Ali Shah was a well-known scholar of Wahdat-ul-Wujud. Pir Meher Ali Shah gave world fame to Khanqah Golra Sharif. His poetry also plays an important role in this fame. Pir Meher Ali Shah was an expert in many languages. He tried typing in Arabic, Persian,Urdu and Punjabi. Peer Moinuddin Geelani, the grandson of Pir Meher Ali Shah, who grew up in this special atmosphere of poetry and speech, also made poetry and speech his field. His natural inclination was towards poetry. Pir Moinuddin Geelani has also experimented in ghazal poetry as well as in hymns, naat and manqbat. His ghazals also cover traditional and classical themes. Ghazal is the real field of Pir Moinuddin Geelani. The fourth part of his poetry collection "Israr Al-Mushtaq" is about generations.